Stability Analysis Of Earth Dam Slopes Subjected To Earthquake Using ERT Results Interpretation - Eko Andi Suryo (Rekayasa Sipil, 2017)
Earth Dam stability can be affected significantly by the existence of excessive leakage. This is due to decreasing of shear strength of the dam material and additional overturning moment. In such scenario, the non-destructive soil investigation method is needed to analyze the stability of earth dam in current condition. This paper examines the use of Electrical Resistivity Tomography (ERT) to investigate soil layers and to measure parameters of soil shear strength indirectly. First survey was carried out at dam crest and downstream using Wenner Configuration along profile lines at electrode spacing of 5 m. There were 5 profile lines of 180m long each and 10m distance of spacing. Furthermore, two profiles lines at weak cross-section based on its resistivity soil values were undertaken. Laboratory tests were conducted to determine relationship between resistivity value, moisture content, cohesion and angle of friction for each type of dam materials. From the ERT results and lab testing, a model dam can be obtained using current material parameters to perform stability analysis of dam subjected to earthquake. The lowest FOS was found at the upstream side about 1.15 and at the downstream side about 1.14 after applying seismic load of 100 years return period.